2017
DOI: 10.1111/jep.12821
|View full text |Cite
|
Sign up to set email alerts
|

The impact of improving access to primary care

Abstract: ObjectivesTo measure the size and timing of changes in utilization and costs for employees and dependents who had major access barriers to primary care removed, across an 8‐year period (2007 to 2014).Study design and methodsRetrospective observational study examining patterns of utilization and costs before and after the implementation of a worksite medical office in 2010. The worksite office offered convenient primary care services with no travel from work, essentially guaranteed same day access, and no co‐pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
(66 reference statements)
0
19
0
1
Order By: Relevance
“…Inadequate or inappropriate health care utilization of certain services may lead to poorer health, higher health inequalities, and higher healthcare expenditures [ 49 , 50 ]. Ensuring, for example, equal access to primary care, equal quality of care and orienting all patients efficiently through the healthcare system could increase preventive care and reduce unnecessary hospitalizations and ED visits [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate or inappropriate health care utilization of certain services may lead to poorer health, higher health inequalities, and higher healthcare expenditures [ 49 , 50 ]. Ensuring, for example, equal access to primary care, equal quality of care and orienting all patients efficiently through the healthcare system could increase preventive care and reduce unnecessary hospitalizations and ED visits [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 37 , 38 All four studies found statistically significant improvements in health outcomes; three of these studies did not result in higher spending (see Table 2 ). 35 , 36 , 38…”
Section: Resultsmentioning
confidence: 99%
“…In addition, only one article in our review analyzed the creation and implementation of an onsite medical office whereby employees and dependents could acquire preventive health care services with no copay. 36 The provision of onsite health care can be a tremendous investment for employers, but for employees and their families it can serve as an efficient conduit to care by removing obstacles such as travel, waiting periods, and payment. A 2018 Mercer survey found that a third of large employers with 5000 or more employees had established worksite clinics—an increase from 25% in 2012—and saw this as a valuable venture to address basic and chronic health problems in their workforce and keep medical costs down.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing barriers to healthcare access, especially those related to adequate receipt of primary care, is critically important for this high-need population. Research has shown that primary care plays a significant role in being a gateway to the healthcare system, reducing future healthcare use, and overall better health outcomes (Glass et al, 2017; Shi, 2012; Starfield et al, 2005). Further research on how adults on the autism spectrum interact with healthcare systems is warranted.…”
Section: Discussionmentioning
confidence: 99%